PENGEMBANGAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN PENCAPAIAN ILMU-AMALIAH DAN AMAL-ILMIAH DI SMPN I CUGENANG - Farhan, Muhamad (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2016)
The research was based on the fact that Islamic Education subject was ineffective to make the students capable to apply it in the real world. Prayer learning was still very theoritical-abstract learning by the brain and merely knowledge. This research aimed to reveal and formulize the contextual learning model design of prayer materials in order to improve the achievement of applicable-knowledge and knowledge-based virtues. The approach taken was a combination of quantitative research and qualitative research using research and development (RD) method. Data were collected through participatory observation, documentation study, in-depth interview, and questionnaire. The research result is a contextual learning model of Islamic Education Subject can improve the achievement of applicable-knowledge and knowledge-based virtues in prayer learning. This can be seen from the students’ improvement of the learning result achievement, and the application of prayer values in students’ daily lives.